2015
DOI: 10.1097/scs.0000000000001806
|View full text |Cite
|
Sign up to set email alerts
|

Extradural Ossification Following Epidural Hematoma in Children

Abstract: There has been a profound increase in the number of patients undergoing head computed tomography after minor injuries and the identification of epidural hematomas has risen concurrently. Although emergent craniotomy and evacuation has been the conventional standard for management, some epidural hematomas can be managed nonoperatively in carefully selected patients. Because of the difficulty in clinically monitoring epidural hematoma absorption and resolution because of the attributed risks of imaging radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In combination, these two factors might play a fundamental role in slow EDH growth and minor symptoms as 60% of children and 85% of infants with EDHs show no signs of deterioration at the time of injury and are frequently diagnosed with a chronic form. Conservative management of EDH in asymptomatic children relies on the abovementioned pathophysiological mechanisms [13, 21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In combination, these two factors might play a fundamental role in slow EDH growth and minor symptoms as 60% of children and 85% of infants with EDHs show no signs of deterioration at the time of injury and are frequently diagnosed with a chronic form. Conservative management of EDH in asymptomatic children relies on the abovementioned pathophysiological mechanisms [13, 21].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of EDH calcification, and the timing thereof, is still a matter of debate [13, 22-39]. Ergodan et al [27] reported early signs of calcification around an EDH 10 days after the trauma, suggesting a role for the acute inflammatory response in EDH calcification [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these symptoms were noted during Mozart's last illness. Calcification of CSH is found in 0.3-2.7% of CSH cases and generally found in children and young adults, 18 as was likely seen in Mozart at the age of 35.…”
Section: Chronic Subdural Hematomamentioning
confidence: 96%